Natural sodium bentonite clay with improved rheological properties

The method of treating natural clay materials with sodium bentonite by removing impurities and spray drying enhances the clay's thickening efficiency and dispersion in aqueous formulations, addressing the need for improved rheological properties.

JP2025512954AActive Publication Date: 2025-04-22BYK CHEMIE GMBH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024559148
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-04-06
Filing Date
2023-04-03
Publication Date
2025-04-22
Estimated Expiration
2043-04-03

AI Technical Summary

Technical Problem

There is a need for bentonite clays with improved rheological properties, particularly those that exhibit enhanced thickening efficiency in aqueous formulations, and can be easily and quickly dispersed in water with reduced shear forces.

Method used

A method involving the preparation of an aqueous slurry of natural clay materials containing sodium bentonite, removal of non-sodium bentonite impurities, and subsequent spray drying to produce solid treated sodium bentonite clay with specific ion exchange content.

Benefits of technology

The treated bentonite clays demonstrate improved thickening efficiency and easier dispersion in aqueous formulations, reducing the need for shear forces and resulting in superior rheological control.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025512954000001
    Figure 2025512954000001
  • Figure 2025512954000002
    Figure 2025512954000002
  • Figure 2025512954000003
    Figure 2025512954000003
Patent Text Reader

Abstract

Bentonite clay having improved rheological properties is provided. The present invention relates to a method for treating a natural clay material comprising sodium bentonite, the method comprising the steps of: i) preparing an aqueous slurry of the natural clay material comprising sodium bentonite; ii) removing non-sodium bentonite impurities from the aqueous slurry; and iii) removing the aqueous solution from the aqueous slurry by spray drying in a spray dryer to prepare a solid treated sodium bentonite clay.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for treating natural clay materials including sodium bentonite, to the treated natural sodium bentonite clay obtained by this method, to uses of the treated natural sodium bentonite clay, and to a method for controlling the rheology of aqueous compositions. [Background technology]

[0002] The different bentonite types are each named based on their dominant cation. For industrial purposes, two main classes of bentonite are recognized: sodium and calcium bentonite. Sodium bentonite is the more valuable, while calcium bentonite is more common. Naturally occurring sodium bentonites are typically not available in high purity. Typically, they carry significant amounts of inert minerals as impurities in the mineral, which impairs their use as rheological additives.

[0003] Natural calcium bentonite can be converted to sodium bentonite by an ion exchange process, called sodium enrichment or sodium activation, to exhibit many of the properties of sodium bentonite. As is commonly practiced, this means adding 5-10% of a soluble sodium salt (e.g. sodium carbonate) to wet calcium bentonite, mixing well, and allowing a period of time to allow ion exchange to occur and for water to remove the exchanged calcium. Some properties of sodium enriched calcium bentonite, such as viscosity and fluid loss of suspension, are not completely equivalent to those of natural sodium bentonite. For example, residual calcium carbonate formed if the exchanged cations are not sufficiently removed can result in poor performance of artificial sodium bentonite.

[0004] CN111269606A describes a method for modifying calcium bentonite powder to sodium bentonite powder. The method involves treating calcium bentonite with a source of sodium cations in the presence of water, preparing an aqueous slurry, followed by centrifugation, pH adjustment, and drying.

[0005] CN102283860A relates to a method for preparing a montmorillonite blend preparation, which belongs to the technical field of pharmaceuticals. The examples describe the treatment of bentonite with water, the removal of sand, and the spray drying of the resulting suspension. Summary of the Invention [Problem to be solved by the invention]

[0006] There is a continuing need to provide bentonite clays with improved rheological properties, particularly bentonites that exhibit improved thickening efficiency in aqueous formulations. Furthermore, it is highly desirable that the clays can be easily and quickly dispersed in water or aqueous formulations with reduced need for applied shear forces. [Means for solving the problem]

[0007] The present invention provides a method for treating natural clay materials, including sodium bentonite, the method comprising the steps of: i) preparing an aqueous slurry of a natural clay material comprising sodium bentonite; ii) removing non-sodium bentonite impurities from the aqueous slurry; and iii) removing water from the aqueous slurry by spray drying in a spray dryer to prepare a solid treated sodium bentonite clay. Including, The solid treated bentonite clay has an exchangeable sodium ion content of less than or equal to 100 mmol / 100 g and an exchangeable calcium ion content of less than or equal to 18 mmol / 100 g, calculated on the dry weight of the clay. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] The method of the present invention provides a treated bentonite clay with improved thickening efficiency in water-based formulations. Furthermore, the treated clay can be easily and quickly dispersed in water or aqueous formulations with reduced need for applied shear forces.

[0009] The starting materials used in the process of the present invention are natural clay materials, including sodium bentonite, which are materials obtained from clay minerals and which have not been treated or modified other than by physical methods, such as by grinding or sieving to obtain a desired particle size.

[0010] Bentonite is a natural clay mineral, the main component being montmorillonite. Generally, bentonite contains montmorillonite in the range of 30-90% by weight. The montmorillonite present in bentonite is aluminium silicate in the form of platelets stacked on top of each other. The platelets are typically slightly negatively charged. Thus, they carry cations (positive ions) in the interlayers between the platelets to compensate for the negative charge of the layers. Their applications are typically due to their high surface area and platelet-like structure, which gives them certain advantages in gelling water or solvents, or in adsorbing certain substances, or in providing barrier properties. In most of these applications, separation of the platelets into single or small laminated platelets is required to achieve the best properties. Bentonite can provide this swelling to the platelets when the interlayer cations are singly charged, especially when the interlayer cations are sodium or lithium. Bentonite clay, which carries mainly divalent cations between its layers, Ca and Mg ions, is slightly swelling and the single platelets of aluminum-silicate cannot be completely removed from each other in water.

[0011] The natural clay material containing sodium bentonite used as the raw material of the present invention generally has a certain sodium ion content, which is suitably expressed as the content of sodium ions exchangeable by ammonium chloride. Typically, the natural clay material containing sodium bentonite contains sodium cations in an amount of at least 20 mmol / 100 g, as determined by ion exchange with ammonium chloride.

[0012] The sodium ion content can be determined by a method involving refluxing the natural clay material in water with an excess of ammonium chloride for one hour, followed by filtration and analysis of the filtrate by inductively coupled plasma optical emission spectroscopy (ICP-OES).

[0013] In a preferred embodiment, the natural clay material comprising sodium bentonite comprises sodium cations in an amount of at least 30 mmol / 100 g, even more preferably at least 40 mmol / 100 g. Generally, the amount of sodium cations is in the range of 20 mmol / 100 g to 100 mmol / 100 g, preferably in the range of 30 to 90 mmol / 100 g.

[0014] A higher content of exchangeable sodium ions indicates a higher content of sodium bentonite in the natural clay material, which is desirable because it means that less non-sodium bentonite raw material needs to be removed.

[0015] In the context of the present invention, the natural clay material containing sodium bentonite preferably has a swelling volume of 12 ml or more, determined by adding 2.0 g of the natural clay material containing sodium bentonite to 100 ml of deionized water. Generally, a higher swelling volume indicates a higher content of sodium bentonite in the natural clay material, which is preferred. In some embodiments, the natural clay material containing sodium bentonite preferably has a swelling volume of 15 ml or more, or 20 ml or more, for example 25 ml or more, or 30 ml or more. The swelling volume is generally 70 ml or less, or 60 ml or less.

[0016] The swelling volume is suitably determined visually. For this purpose, a measuring cylinder is filled with 100 ml of deionized water and 2 g of each clay material is added to the water in portions during 30 minutes. 60 minutes after the last portion of clay material has been added, the volume of swollen material in the measuring cylinder can be determined visually.

[0017] The sodium bentonite-containing natural clay material used according to the present invention comprises sodium bentonite as well as other materials collectively referred to as non-sodium bentonite impurities. Suitably, the sodium bentonite-containing natural clay material comprises sodium bentonite in an amount of 10-90% by weight, calculated on the dry weight of the natural clay material. In a preferred embodiment, the content of sodium bentonite in the natural clay material is in the range of 30-90% by weight, calculated on the dry weight of the natural clay material.

[0018] The content of sodium bentonite in the natural clay material can be determined by removing the non-sodium bentonite impurities from the natural clay material by a method of dispersing the natural clay material in water, followed by centrifugation at 3700 g for 10 minutes to remove the non-sodium bentonite impurities, and drying the remaining aqueous phase.

[0019] The content of non-sodium bentonite impurities in the natural clay material is suitably in the range of 10-90% by weight, preferably 10-60% by weight, calculated on the dry weight of the natural clay material.

[0020] In most embodiments, the non-sodium bentonite impurities include at least one of feldspar, calcite, mica, quartz, cristobalite, dolomite, and calcium bentonite.

[0021] In step i) of the method of the present invention, an aqueous slurry of the natural clay material, including sodium bentonite, is prepared. The aqueous slurry can be prepared by mixing the natural clay material with water in a suitable container. The order of addition of the natural clay material and the water to the container is not important. It is also possible to introduce the water and the natural clay material simultaneously into the container. Tap water or water of similar purity is very suitable for use. If necessary, water of higher purity or deionized water can be used. However, from an economic point of view, the use of deionized water is less preferred.

[0022] Typically, the aqueous slurry contains the natural sodium clay material, including sodium bentonite, in an amount of 2-20% by weight, calculated based on the weight of the aqueous slurry. The method can also be carried out in an embodiment where the amount of the natural sodium clay material, including sodium bentonite, is less than 2% by weight of the aqueous slurry, but such an embodiment is less attractive from an economic point of view due to the large amount of water that must be handled. If the amount of the natural sodium clay material, including sodium bentonite, in the aqueous slurry exceeds 20%, the viscosity of the slurry becomes very high, which may impair the handling of the aqueous slurry, such as stirring and pumping. In a preferred embodiment, the aqueous slurry contains the natural sodium clay material, including sodium bentonite, in an amount of 3-15% by weight, calculated based on the weight of the aqueous slurry.

[0023] In most embodiments, shear force is applied to the aqueous slurry prepared in step i) of the method of the present invention. The shear force can be applied by means known to those skilled in the art, such as a mixer, agitator or dissolver, or a combination thereof. The application of shear force can reduce the particle size of the slurry and / or result in a more uniform particle size distribution within the slurry.

[0024] In a preferred embodiment, at least one dispersing additive is present during the preparation of the aqueous slurry of the natural clay material containing sodium bentonite. The presence of the dispersing additive reduces the viscosity of the slurry at a given content of natural clay material containing sodium bentonite and water. Furthermore, the presence of the dispersing additive can also improve the separation of non-sodium bentonite impurities in step ii) of the method of the present invention. Thus, the dispersing additive can improve the efficiency of the method.

[0025] Preferably, the dispersion additive comprises at least one of an organic polymer or oligomer and an inorganic phosphate or polyphosphate. Suitable organic polymers or oligomers include linear and branched polymers or oligomers having pendant or terminal carboxylic acid groups or salts thereof, phosphoric acid groups or salts thereof, or phosphonate groups. Suitable polymer or oligomer types include polyester and polyacrylate polymers and oligomers. The weight average molecular weight of the polymer or oligomer is generally in the range of 200 to 250,000 g / mol, preferably 500 to 50,000 g / mol.

[0026] When present, the amount of dispersing additive is suitably in the range of 0.5 to 5.0 wt.%, calculated based on the weight of the natural clay material including sodium bentonite. If the dispersing additive is used in an amount less than 0.5 wt.%, the beneficial effects of the dispersing additive may not be fully achieved.

[0027] In some embodiments, the dispersing additive may contain sodium ions, however, the amount of sodium ions introduced with the dispersing additive is always lower than the amount of sodium ions required for sodium activation of calcium bentonite.

[0028] In step ii) of the process of the present invention, non-sodium bentonite impurities are removed from the aqueous slurry. Non-sodium bentonite impurities are mainly present in the aqueous slurry in the form of solid particles or incompletely swollen material, which can be separated from the aqueous phase by physical separation processes commonly known to those skilled in the art. Examples of suitable separation processes include settling, decantation, flotation, and centrifugation. If desired, such processes can be combined or performed sequentially.

[0029] The removed non-sodium bentonite impurities include most of the crystalline impurities and low swelling amorphous minerals and low swelling clays such as calcium bentonite. The better swelling sodium bentonite is primarily not removed and remains in the slurry.

[0030] As mentioned above, the non-sodium bentonite impurities that are removed typically include at least one of feldspar, calcite, mica, quartz, cristobalite, dolomite, and calcium bentonite.

[0031] After the separation step, the aqueous slurry is recovered and the water is removed from the aqueous slurry by spray drying in a spray drying apparatus to prepare a solid treated sodium bentonite clay.

[0032] Optionally, shear forces may be applied to the aqueous slurry prior to removal of water by spray drying. This optional processing step can use any commonly known technique for applying shear force. Examples of suitable methods for applying shear force include processing in a high speed dissolver or forcing the slurry through a hole under pressure.

[0033] In step iii) of the process of the present invention, water is removed from the aqueous slurry by spray drying in a spray dryer to prepare a solid treated sodium bentonite clay.

[0034] Spray drying is an essential feature of the process of the present invention, as it has been found that drying methods other than spray drying result in solid treated sodium bentonite clay having inferior properties.

[0035] A spray dryer takes in a liquid stream and separates the solute or suspension as solids and the solvent into steam. The solids are usually collected in a drum or cyclone. The liquid input stream is sprayed through a nozzle into a hot steam stream and vaporized. Solids are formed as moisture leaves the droplets quickly. Nozzles are usually used to make the droplets as small as possible, maximizing heat transfer and the evaporation rate of the water. Droplet sizes generally range from 20 to 180 μm depending on the nozzle. There are two main types of nozzles: high pressure single-fluid nozzles (50 to 300 bar) and two-fluid nozzles, where one fluid is the liquid for drying and the second is a compressed gas (generally air at 1 to 7 bar). Instead of using a nozzle to atomize the liquid, a rotary atomizer can also be used. Rotary atomizers work on the principle of centrifugal energy, which is used to generate the high relative velocities between the fluid and the air that are essential for atomization. Rotary atomizers comprise a rotary surface, which may be in the form of a flat or vaned disk, a cup, or a slotted wheel. The liquid first flows radially outward within the disk and then exits the outer edge of the disk at a relatively very high velocity. Atomization depends on the liquid flow rate and the rotational speed of the disk.

[0036] Spray dryers can dry articles very quickly compared to other drying methods. They also turn a solution (or slurry) into a dry powder in a single step, which simplifies the process.

[0037] The inlet air temperature of the spray drying apparatus is generally in the range of 150 to 600°C, preferably in the range of 200 to 450°C.

[0038] The spray drying process results in the removal of water to provide solid particles of treated sodium bentonite clay. Generally, the treated sodium bentonite clay still contains a residual amount of water, for example not more than 20.0% by weight, calculated on the total weight of the treated sodium bentonite clay. Preferably, the water content is in the range of 0.1-18.0% by weight, more preferably in the range of 0.5-15.0% by weight, calculated on the total weight of the treated sodium bentonite clay.

[0039] The present invention also relates to a treated sodium bentonite clay obtainable or obtained by the process of the present invention.

[0040] The treated sodium bentonite clay exists in the form of particles. The particles typically have a shape having similar magnitudes in all three dimensions, as opposed to a needle-like or platelet-like shape, where one or two of the dimensions significantly exceed the others. Generally, the length, width, and height of the particles differ from each other by less than 35%.

[0041] Suitably the particles have a d50 number average particle size, as determined by laser diffraction, in the range of 5 to 60 μm, preferably 8 to 40 μm.

[0042] The particles typically have a morel-like structure, meaning that they have an irregular surface characterized by a network of ridges.

[0043] The treated sodium bentonite clay obtained by the process of the present invention suitably has a content of crystalline impurities of less than 10% by weight, preferably less than 5% by weight, more preferably less than 3% by weight.

[0044] The treated sodium bentonite clay has an exchangeable sodium ion content of less than 100 mmol / 100 g and an exchangeable calcium ion content of less than 18 mmol / 100 g, calculated on the dry weight of the clay.

[0045] The amount of exchangeable sodium ions is preferably in the range of 50-100 mmol / 100 g, and even more preferably in the range of 50-90 mmol / 100 g, of the treated sodium bentonite.

[0046] The amount of exchangeable calcium ions is preferably in the range of 2-18 mmol / 100 g, even more preferably in the range of 2-15 mmol / 100 g, of the treated sodium bentonite.

[0047] The amount of exchangeable sodium and calcium ions is suitably determined by a method that includes refluxing the treated clay material with excess ammonium chloride in water for 1 hour, followed by filtering and analyzing the filtrate by inductively coupled plasma optical emission spectroscopy (ICP-OES). Excess ammonium chloride means that ammonium chloride is used in an amount greater than the exchangeable ions present in the treated clay material. Suitably, 120 mg of the treated clay material is refluxed with 8 ml of an aqueous solution of ammonium chloride at a concentration of 2 mol / l.

[0048] The treated sodium bentonite clay obtainable by the method of the present invention is very suitable for controlling the rheology of aqueous compositions. In particular, the treated sodium bentonite clay can be easily dispersed in many different aqueous compositions and induces desirable rheological effects. Therefore, the present invention also relates to the use of the treated sodium bentonite clay for controlling the rheology of aqueous compositions.

[0049] The present invention further relates to a method for controlling the rheology of an aqueous composition, which method comprises adding to the aqueous composition the treated sodium bentonite clay obtainable by the method of the present invention.

[0050] In the above uses or methods, the treated sodium bentonite clay is suitably added to the aqueous composition in an amount ranging from 0.1 to 7.0% by weight, preferably from 0.1 to 5.0% by weight, calculated on the total weight of the aqueous composition.

[0051] When treated sodium bentonite clay is added to an aqueous composition, the viscosity of the aqueous composition generally increases. The higher the amount of treated sodium bentonite clay, the higher the viscosity generally. In some embodiments, the addition of treated sodium bentonite clay causes thixotropic behavior of the aqueous composition.

[0052] The aqueous composition may be any liquid aqueous composition that should be made viscous or thixotropic. An aqueous composition is a composition in which the main or only liquid diluent used is water. Preferably, the aqueous composition contains less than 35% by weight, less than 25% by weight, less than 20% by weight, or even less than 10% by weight of (volatile) organic solvent, based on the total weight of water and organic solvent in the liquid formulation. In some embodiments, the aqueous composition does not contain organic solvent. The aqueous composition may contain water-soluble organic or inorganic compounds, for example ionic compounds such as salts.

[0053] Examples of suitable aqueous liquid compositions include coating compositions, (pre)polymer compositions, pigment concentrates, ceramic products, sealants, cosmetic preparations, adhesives, casting compounds, lubricants, inks, cleaning agents, liquids for use in gas or oil production, putties, metal working fluids, sprayable liquids, e.g. deposition aids for use in crop protection, wax emulsions, liquids for use in energy storage media such as batteries, liquids for use in electrical or electronic components, casting or potting compositions, and building materials.

[0054] The aqueous compositions, which are coating compositions or inks, can be used in various application areas such as automotive coatings, architectural coatings, protective coatings (such as marine or bridge coatings), can and coil coatings, wood and furniture coatings, industrial coatings, plastic coatings, wire enamels, food and seed coatings, leather coatings (for natural and artificial leather), color resists (such as those used for LC display devices), etc. Coating materials typically include paste-like materials with a high content of solids and a low content of liquid components, such as pigment pastes or effect pigment pastes (using pigments based on aluminum, silver, brass, zinc, copper, bronze such as copper, iron oxide-aluminum); other examples of effect pigments are interference pigments and pearlescent pigments, such as metal oxide-mica pigments, bismuth oxide chloride or basic lead carbonate.

[0055] The cosmetic composition can be any type of aqueous liquid composition used for personal care and health care purposes. Examples are lotions, creams, pastes such as toothpaste, foams such as shaving foam, gels such as shaving gels and shower gels, pharmaceutical compounds in gel-like delivery form, hair shampoos, liquid soaps, nail polish, lipsticks, and hair coloring lotions.

[0056] A preferred wax emulsion is an aqueous dispersion of wax particles formed from waxes that are solid at room temperature.

[0057] Sprays, preferably those used as deposition aids, can be equipped with the treated sodium bentonite of the present invention to achieve drift reduction. They can contain, for example, fertilizers or herbicides, fungicides, and other pesticides.

[0058] The formulations used for construction purposes can be materials that are liquid or pasty during handling and processing, these water-based materials are used in the construction industry and become solid after curing time, e.g., hydraulic binders like concrete, cement, mortar / plaster, tile adhesives, and gypsum.

[0059] Metalworking fluids are water-based compositions used in the treatment of metals and metal parts. Examples are cutting fluids, drilling fluids (used for metal drilling), mold release agents (mainly water-based emulsions, e.g., in aluminum die casting and casting applications), foundry cleaning fluids, foundry coatings, and liquids used for the surface treatment of metals (surface finishing, surface cleaning, plating, etc.).

[0060] Lubricants are water-based compounds used for lubricating purposes, i.e. to reduce wear and friction losses, or to improve cooling, force transmission, vibration damping, sealing effect, and corrosion protection. The liquid formulations used in gas and oil production are water-based formulations used to develop and exploit reserves. Water-based drilling fluids or "drilling muds" are preferred examples. An example application is hydraulic fracturing.

[0061] Cleaning agents can be used to clean various kinds of objects. They help remove contaminants, residual soils, and attached debris. Cleaning agents also include detergents (especially for cleaning textiles, their precursors, and leather), cleaning agents and polishes, laundry formulations, fabric softeners, and personal care products.

[0062] Preferred aqueous compositions include aqueous coating compositions, aqueous compositions containing hydraulic binders, aqueous cleaning compositions, and aqueous personal care compositions.

[0063] The aqueous compositions described above may contain other components and additives commonly used in aqueous compositions, such as organic co-solvents, crosslinkers, defoamers, dispersing aids, and UV stabilizers. Although the treated sodium bentonite according to the present invention provides excellent thickening properties, it can be used in combination with other rheology control agents, if desired.

[0064] Examples of other rheology control agents include polysaccharides (such as cellulose derivatives, guar, xanthan, etc.), urea compounds, (poly)amides, polyacrylates (such as alkali-soluble or swellable emulsions), or associative thickeners (such as polyurethane thickeners, aminoplast-based thickeners, hydrophobically modified alkali-soluble emulsion-type thickeners, etc.).

[0065] The treated sodium bentonite of the present invention can be used as an adsorbent in certain compositions, for example to absorb undesirable impurities. EXAMPLES

[0066] Example 1: Naturally occurring sodium bentonite raw clay is commercially available as "Natural Sodium Bentonite Powder", is soda ash free, has a moisture content of 8% by weight and a montmorillonite content of over 65% by weight. The analyzed swelling volume in deionized water was 19 ml / 2 g. The crystalline impurities were analyzed by powder x-ray diffraction. The amount of crystalline impurities was 12% by weight.

[0067] 250 kg of natural sodium bentonite powder was slurried in 4800 kg of tap water with vigorous stirring using a propeller mixer and a serrated dissolving disk for 30 minutes. The slurry was then refined by removing crystalline impurities and non-swelling mineral parts by passing it through a Flottweg decanter centrifuge with a feed centrifugal force of about 3700G. About 1 / 3 of the initial clay content was removed by this decanter centrifugation process. The removed material includes most of the crystalline impurities, low swelling amorphous minerals, low swelling clays such as calcium bentonite. The better swelling sodium bentonite is mainly not removed and remains in the slurry. The total crystalline impurities were reduced to about 2% by this treatment.

[0068] To ensure complete dispersion, the resulting slurry was further passed through a Manton-Gaulin homogenizer at a pressure of 150 bar.

[0069] The resulting slurry was dried in an Anhydro spray dryer with an inlet drying air temperature of 380°C. The spray feed rate was adjusted to achieve a moisture content of 6% by weight in the resulting dry powder. The outlet temperature of the spray dryer ranged from 70 to 100°C. The resulting powder had a number average d50 particle size of 15 μm. The treated sodium bentonite had an amount of exchangeable sodium ions of 61 mmol / 100 g and an amount of exchangeable calcium ions of 11 mmol / 100 g, calculated based on the dry weight of the material.

[0070] Example 2: 400 kg of natural sodium bentonite powder was slurried in a mixture of 3600 kg tap water and 12 kg BYK-155 / 35 polyacrylate dispersant. For further processing, the same procedure as in Example 1 was followed. The treated sodium bentonite had an exchangeable sodium ion amount of 83 mmol / 100 g and an exchangeable calcium ion amount of 12 mmol / 100 g, calculated based on the dry weight of the material.

[0071] Example 3: 400 kg of natural sodium bentonite powder was slurried in a mixture of 3600 kg tap water and 4 kg Na-pyrophosphate dispersant. For further processing, the same procedure as in Example 1 was followed.

[0072] Comparative Example 1: Natural sodium bentonite powder, sourced from a mineral mine, was ground without refinement to the same fineness and moisture as in Example 1. The treated sodium bentonite had an exchangeable sodium ion content of 72 mmol / 100 g and an exchangeable calcium ion content of 46 mmol / 100 g, calculated based on the dry weight of the material.

[0073] Comparative Example 2: The refined and homogenized slurry from Example 1 (before spray drying) was lab dried to less than 12% moisture in a lab drying oven at 70° C. and ground to the same fineness as Example 1 in a lab mill.

[0074] Comparative Example 3: The refined and homogenized slurry from Example 1 (before spray drying) was dried in a drum dryer to less than 12% moisture and ground in a lab mill to the same fineness as Example 1.

[0075] Comparative Example 4: Optigel CK: artificial sodium bentonite produced by alkaline soda activation of calcium bentonite, commercially available from BYK-Chemie GmbH, was treated in the same manner as in Example 1. The treated sodium bentonite had an amount of exchangeable sodium ions of 135 mmol / 100 g and an amount of exchangeable calcium ions of 20 mmol / 100 g, calculated on the dry weight of the material.

[0076] Test results Underwater viscosity Clay (3, 5% or 5% calculated on the clay dry weight) was added to deionized water at room temperature in a 70 mm diameter glass beaker to prepare a suspension with a total of 200 g water and clay. The addition was done slowly with stirring at a mixing speed of 930 rpm using a Pendraulik 4 cm diameter toothed cowl disk attached to a Pendraulik lab stirrer LD 50. Upon complete addition, the dissolution rate was increased to 2800 rpm for a dispersion time of 10 minutes. After dispersion, the viscosity was measured at 10 rpm on a Brookfield DV II. The reading was taken after a measurement time of 2 minutes. The glass beaker was then covered and stored at room temperature for the indicated storage time (e.g., 1 hour, 1 day, 1 week) and the measurement was taken again.

[0077] [Table 1]

[0078] [Table 2]

[0079] The results in Table 1 demonstrate that the thickening effect of the treated sodium bentonite according to the invention occurs much faster than the thickening effect of the comparative sodium bentonite.

[0080] Alpina Weiss Paint 100 g of Alpina weiss Innenfarbe "Das Original" (flat emulsion paint, DAW SE) and 0.2 g of BYK-035 and 24.43 g of the 3,5% aqueous formulation (pregel) according to table 1 or 17.0 g of the 5% aqueous formulation (pregel) according to table 1 + 6.8 g of deionized water were added to a Delbrouck beaker no. 211. This was mixed for 5 minutes at 2800 rpm in a Pendraulik lab stirrer LD 50 with a toothed cowl disc of 4 cm diameter. It was then covered and stored at room temperature for 1 day. The viscosity was measured on a Brookfield DV II at 10 rpm. The values ​​were read after a measuring time of 2 minutes.

[0081] [Table 3]

[0082] [Table 4]

[0083] From Table 2 it can be seen that the sodium bentonite treated according to the invention provides much better thickening in water-based paints than the sodium activated Ca-bentonite treated in the same way.

[0084] Determining the sag resistance of white paints A white paint was prepared from the ingredients listed in Table 3 below.

[0085] [Table 5]

[0086] Sag resistance measurement Sag resistance was measured according to ASTM D440-84. This standard test method utilizes a drawdown blade with a series of notches with successively greater clearance. The coating was applied to the test chart with a multi-notch applicator. The chart was immediately suspended vertically and the drawdown strip was horizontal. Sag resistance is measured from the drawdown after the film has completely dried. The result indicates the maximum layer thickness that can be applied without sagging of the paint. The results are summarized in Table 4 below:

[0087] [Table 6]

[0088] From Table 4 it can be concluded that the treated sodium bentonite clay according to the invention provides better sag resistance in water-based paints than the comparative bentonite clay.

Claims

1. 1. A method for treating natural clay materials comprising sodium bentonite, comprising the steps of: (i) preparing an aqueous slurry of a natural clay material comprising sodium bentonite; (ii) removing non-sodium bentonite impurities from said aqueous slurry; and (iii) removing water from said aqueous slurry by spray drying in a spray dryer to prepare a solid treated sodium bentonite clay; Including, the solid treated bentonite clay has an exchangeable sodium ion content in an amount of less than or equal to 100 mmol / 100 g and an exchangeable calcium ion content in an amount of less than or equal to 18 mmol / 100 g, calculated on the dry weight of the clay; method.

2. 2. The method of claim 1, wherein the natural clay material comprising sodium bentonite has a swelling volume of 12 ml or greater as determined by adding 2.0 g of the natural clay material comprising sodium bentonite to 100 ml of deionized water.

3. 3. The method of claim 1 or 2, wherein the non-sodium bentonite impurities include at least one of feldspar, calcite, mica, quartz, cristobalite, dolomite, and calcium bentonite.

4. 4. The method according to any one of claims 1 to 3, wherein the natural clay material comprising sodium bentonite has a content of non-sodium bentonite impurities in the range of 10 to 90% by weight, preferably 10 to 60% by weight.

5. The method according to any one of claims 1 to 4, wherein in step (i) a shear force is applied to the aqueous slurry.

6. A method according to any one of claims 1 to 5, wherein a dispersing additive is present during preparation of the aqueous slurry of natural clay material comprising sodium bentonite.

7. The method of claim 6 , wherein the dispersion additive comprises at least one of an organic polymer and an inorganic phosphate.

8. The method of any one of claims 1 to 7, wherein removing non-sodium bentonite impurities from the aqueous slurry is carried out by settling or centrifugation.

9. A method according to any one of the preceding claims, wherein the inlet air temperature of the spray drying apparatus is in the range of 150 to 600°C.

10. 10. The method according to any one of claims 1 to 9, wherein the residual moisture content in the solid treated sodium bentonite clay is not more than 20% by weight, calculated on the total weight of the solid treated sodium bentonite clay.

11. A treated sodium bentonite clay obtainable by the method according to any one of claims 1 to 10.

12. 12. The treated sodium bentonite clay of claim 11, wherein the treated sodium bentonite clay is present in the form of particles having morel-like structures.

13. 13. The treated sodium bentonite clay according to claim 11 or 12, wherein the particles have a d50 number average particle size in the range of 5 to 60 μm as measured by laser diffraction.

14. Use of the treated sodium bentonite clay according to any one of claims 11 to 13 for controlling the rheology of an aqueous composition.

15. The use according to claim 14, wherein the aqueous composition is selected from an aqueous coating composition, an aqueous composition comprising a hydraulic binder, an aqueous cleaning composition, and an aqueous personal care composition.

16. 16. Use according to claim 14 or 15, wherein the treated sodium bentonite clay is added to the aqueous composition in an amount ranging from 0.1 to 7.0% by weight, preferably from 0.1 to 5.0% by weight, calculated on the total weight of the aqueous composition.

17. A method for controlling the rheology of an aqueous composition comprising adding to the aqueous composition a treated sodium bentonite clay according to any one of claims 11 to 13.

Citation Information

Patent Citations

  • Production of water flutriated bentonite

    JP1987070222A

  • Method for treating clay for paper coating pigment

    JP1996319436A

  • Modified sodium montmorillonite, its preparation method and use

    JP2012514571A

  • Method of removing hydrous silica from bentonite

    JP2016128375A

  • Ion-exchangeable layered silicate particles, catalyst component for olefin polymerization, catalyst for olefin polymerization, method for producing catalyst for olefin polymerization and method for producing olefin polymer using the same

    JP2022051551A